REVITALISASI ISTILAH TUMBUH-TUMBUHAN LANGKA DALAM PENGAJARAN BAHASA BALI, SEBAGAI UPAYA PELESTARIAN LINGKUNGAN HIDUP (KAJIAN EKOLINGUISTIK) - Suweta, I Made (Bumi Lestari; Vol 13 No 1 (2013), 2013)
Abstract Language associated with the environment around us is highly correlated with ecolinguistics study. Aspects of the direct contact with the rare plants are very important from the point of view ecolinguistics study, therefore very important that the term of rare plants to be revitalized and can be incorporated in teaching, especially in terms of vocabulary learning. The formulation of the problem to be studied are: (1) how the classification of rare plants term in vocabulary of Balinese language? and (2) how to revitalize the term of rare plants in the learning of Balinese language vocabulary ? The method used to discuss this paper is listening vocabulary of rare plants as possible, either through speech community understanding in Balinese language and literature over the script through the manuscrift of medicinal plants. The analysis was done by descriptive qualitative through integration between inductive and deductive method. This paper produces some results of the study as follows. Classification of rare plants, the term is described as follows: (1) related to Hindu religion, (2) residential building/sanctuary, (3) food/beverage, (4) agriculture/animal husbandry, (5) sacred/magical, (6) drug-medicines. Descriptions in teaching Balinese terms are as follows: (1) the term two syllables, (2) three syllables, (3) four syllables, (4) five syllables, (5) The compound, and (6) repeatedword.
Keywords: Keywords: ecolinguistics, revitalization, language teaching Bali.